2006
DOI: 10.1002/j.0022-0337.2006.70.4.tb04094.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Education and Care for Underserved Patients: An Analysis of Students’ Intentions and Alumni Behavior

Abstract: Inglehart, Dr. phil. habil.Abstract: The U.S. surgeon general's report on oral health stressed the importance of providing dental care to underserved patients. The objectives of this study were to explore a) dental students' intentions and dentists' behavior concerning treating underserved patients, b) their perceptions of their education concerning these patients, and c) the relationship between dental education and their attitudes and behavior. Data were collected from 328 dental students (response rate: 77.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 19 publications
7
88
1
1
Order By: Relevance
“…Didactic lectures were often included with other teaching approaches, such as experiential learning, discussion seminars, problem‐based learning, and community‐based rotations . Scenario‐ and problem‐based learning that use simulations of situations and case studies, respectively, were used to address various topics of interest .…”
Section: Resultsmentioning
confidence: 99%
“…Didactic lectures were often included with other teaching approaches, such as experiential learning, discussion seminars, problem‐based learning, and community‐based rotations . Scenario‐ and problem‐based learning that use simulations of situations and case studies, respectively, were used to address various topics of interest .…”
Section: Resultsmentioning
confidence: 99%
“…Para as faculdades que não explicitaram essa intenção, seus dirigentes expressaram seu interesse em desenvolver módulos de extensão e cursos de especialização aplicados à atenção aos PNE. Atividades de extensão universitária têm sido avaliadas favoravelmente como modalidade de integração entre ensino universitário e atendimento odontológico aos PNE (Kimmelman, 1989;Reed, 1989;Wile;Ferguson, 1992;Nunn et al, 2004;Smith et al, 2006 (Stiefel;Truelove, 1985;Erridge, 1986;Glassman;Miller, 1998;Ettinger, 2000;Ettinger et al, 2004;Gallagher;Fiske, 2007 (Ettinger et al, 2004;Hunter et al, 2004;Conselho Federal de Odontologia, 2005;Gallagher;Fiske, 2007).…”
Section: Associação Paulista De Cirurgiões-dentistas -Apcdunclassified
“…Dentists' willingness to treat the underserved and their behavior can be shaped during dental school (P. L. Davidson, 2009;Smith, Ester, & Inglehart, 2006). More exposure and experience in providing care to the underserved, especially in community settings other than dental school (a.k.a.…”
Section: Study Purpose and Its Significancementioning
confidence: 99%
“…The authors concluded that the level of preparedness (at least perceived preparedness) during dental school affects not only providers' attitude for caring for the underserved but also their actual intention and behavior to treat the underserved. The authors suggested that access to oral health care for underserved patients could potentially be increased if dental students were more overtly educated about the importance of treating patients from all segments of society (Smith et al, 2006). year from dental school, and community assignments influence only a few of these targeted population groups (Kuthy, Heller, Riniker, McQuistan, & Qian, 2007).…”
Section: Attitudementioning
confidence: 99%